(untitled) (Comparatismi, 2025)
This article explores the revolutionary role of women’s authorship in redefining poetry through feminist revisionism and experimental forms such as verbivocovisual poetry. Traditionally, the poetic canon has been shaped by patriarchal structures, with the poet cast in a ‘quasi-priestly role’ (Gilbert, Gubar, 1979). Women’s reclamation of poetic authority thus constitutes an act of resistance. By embracing unconventional forms – collage, visual poetry, and conceptual works – they simultaneously challenge genre constraints and assert their creative agency. Contemporary voices, including Marjorie Perloff and Susan Stanford Friedman, highlight how these redefinitions destabilise traditional hierarchies of authorship and genre. Italian verbivocovisual poets such as Lucia Marcucci, Ketty La Rocca, Giulia Niccolai, Mirella Bentivoglio, and Tomaso Binga have reshaped poetry through multimedia experimentation. By integrating linguistic, visual, and performative elements, they dismantle the exclusivity of the lyric tradition, transforming poetry into a multisensory and politically charged medium. Their works challenge rigid separations between word and image, poetry and visual art, written text and embodied expression, undermining the dominance of a singular, monologic voice. Through appropriation, fragmentation, and conceptual play (including references to mass media and advertising) they expose and resist patriarchal structures embedded in poetic and social discourse. Recognising these experimental works as poetry reconfigures the genre itself, contesting canonical elitism and affirming the plurality of women’s experiences. As Audre Lorde asserted, “poetry is not a luxury”; it is a necessity for survival and transformation, one that women actively reclaim and redefine.